Prosthetic rehabilitation of a hemimandibulectomy patient with the help of implant-retained prosthesis - Tamás Déri; László Kádár (Hungarian Dental Association, 2020)
In the combined maxillo-facial and prosthetic rehabilitation one of the most difficult cases is the complex treatment of the hemimandibulectomy defects. The problem is, that in case of the lost continuity of the mandible's bony base, the support of the later denture is insufficient, and the bone-replacing soft tissues are not able to withstand the load of the denture baseplate. Usually the patients, who have such defects, are completely edentulous, and without rest teeth, the possibilities of making a well-functioning prostheses are not so optimal. On the other hand, some kind of temporomandibular joint disorder will occur, because the normal function is impossible with two separate pieces of the lower jaw. The implant retained removable dentures, especially the overdentures are very good variants of treatment by these kind of defects, because the very disadvantageous clinical-anatomical circumstances don't provide proper retention and stability for the prostheses. With the help of the implants we have the possibility to use ball-, bar-joint, push button or even magnetic retentive systems to avoid the denture's dislocation. Of course, the more implants we can use, the better the result will be. But we can say, just two implants can give so good stability, wich is inconceivable with the conventional edentulousness treatment methods.